Conditional activation of associative semantic structures:forming and transmitting impressions of personality - Nunes, Ludmila Duarte da Silva (2013)
Tese de doutoramento, Psicologia (Cognição Social), Universidade de Lisboa, Faculdade de Psicologia, 2012